2018
DOI: 10.1039/c8qo00499d
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of fluoroalkoxy or fluorophenoxy substituted N-heterocycles from heterocyclic N-oxides and polyfluoroalcohols

Abstract: A novel and efficient approach to introduce fluorine-containing groups into N-heterocycles was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…The investigation of solvents on the model reaction showed that the yields decreased markedly in both DMF and DMSO (28 % and 31 %), and only moderate yields were obtained in CH 2 Cl 2 (55 %), toluene (67 %), H 2 O (40 %) and its co‐solvent (CH 3 CN/H 2 O, v/v=1 : 1) (55 %) (entries 9–14). Alternatively, when the reaction was conducted without the CaCl 2 drying tube, the isolated yield of 3 a (75 %) were remarkably lower than the reaction with CaCl 2 drying tube (83 %) and the byproduct, quinolin‐2(1H)‐one, derived from the C2‐hydroxylation of quinoline N ‐oxide can be easily detected (entry 15) [15a,e] . Moreover, a higher reaction temperature (40 °C, entry 16) or a longer reaction (2 h, entry 17) failed to further elevate the isolated yield of 3 a .…”
Section: Methodsmentioning
confidence: 99%
“…The investigation of solvents on the model reaction showed that the yields decreased markedly in both DMF and DMSO (28 % and 31 %), and only moderate yields were obtained in CH 2 Cl 2 (55 %), toluene (67 %), H 2 O (40 %) and its co‐solvent (CH 3 CN/H 2 O, v/v=1 : 1) (55 %) (entries 9–14). Alternatively, when the reaction was conducted without the CaCl 2 drying tube, the isolated yield of 3 a (75 %) were remarkably lower than the reaction with CaCl 2 drying tube (83 %) and the byproduct, quinolin‐2(1H)‐one, derived from the C2‐hydroxylation of quinoline N ‐oxide can be easily detected (entry 15) [15a,e] . Moreover, a higher reaction temperature (40 °C, entry 16) or a longer reaction (2 h, entry 17) failed to further elevate the isolated yield of 3 a .…”
Section: Methodsmentioning
confidence: 99%
“…2-Aminoarylated and 2-arylated 4-chloroquinoline provided a low yield (30-36%) of the desired product 3c-d. Substitution at the arene ring of quinoline with and 6,7-dimethoxy substituents did not alter the outcome of the reaction and furnished good to excellent yield (55-99%) of C4-fluorinated quinolines 3e-k. was also well-tolerated and gave the fluorinated product in 90% yield at 100 °C. 2-Meth-yl-4,6-dichloroquinoline also afforded excellent yield of the desired product 3l.…”
Section: Paper Synthesismentioning
confidence: 97%
“…10 Hexafluoro-2-propanol (HFIP) as a solvent has been explored in various C-H functionalization methods 11 and it has also recently been used as a source of fluorinating reagent to couple with quinoline C2 position through C-H functionalization. 7 The synthesis of C4 fluoroalkoxy quinoline from 4-haloquinoline and HFIP has not been explored much. 12 Herein, we report the selective C4fluoroalkoxylation of halo quinoline with HFIP through nucleophilic substitution of halogens (Cl, Br, I) at the C4 and C2 position of quinolines.…”
Section: Figure 1 Examples Of Bioactive Quinoline Drugs Containing Fluorine Atomsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar strategy using silver carbonate allowed for the introduction of fluoroalkoxy groups onto quinolines, isoquinolines, and pyridines (Scheme 38). [61] Two byproducts, viz. 2‐bromoquinoline and 2‐quinolinone, were detected when DIPEA was used as the base.…”
Section: Simple C2‐h‐functionalizationmentioning
confidence: 99%